2024
DOI: 10.1007/s00134-024-07362-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrical impedance tomography-guided positive end-expiratory pressure titration in ARDS: a systematic review and meta-analysis

Nickjaree Songsangvorn,
Yonghao Xu,
Cong Lu
et al.

Abstract: Purpose Assessing efficacy of electrical impedance tomography (EIT) in optimizing positive end-expiratory pressure (PEEP) for acute respiratory distress syndrome (ARDS) patients to enhance respiratory system mechanics and prevent ventilator-induced lung injury (VILI), compared to traditional methods. Methods We carried out a systematic review and meta-analysis, spanning literature from January 2012 to May 2023, sourced from Scopus, PubMed, MEDLINE (Ovid), Cochrane, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…EIT represents a transformative advancement in the management of Acute Respiratory Distress Syndrome (ARDS), a condition characterized by acute hypoxemic respiratory failure and noncardiogenic pulmonary edema [12]. The complexity of ARDS, with its diverse lung injury patterns, necessitates precise, real-time imaging to guide therapeutic decisions and interventions [13,14].…”
Section: Eit and Ards: Unveiling Pulmonary Inhomogeneitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…EIT represents a transformative advancement in the management of Acute Respiratory Distress Syndrome (ARDS), a condition characterized by acute hypoxemic respiratory failure and noncardiogenic pulmonary edema [12]. The complexity of ARDS, with its diverse lung injury patterns, necessitates precise, real-time imaging to guide therapeutic decisions and interventions [13,14].…”
Section: Eit and Ards: Unveiling Pulmonary Inhomogeneitiesmentioning
confidence: 99%
“…EIT offers a direct view of how these interventions affect lung ventilation and perfusion in real-time. For instance, research by Songsangvorn et al has demonstrated that EIT-guided PEEP titration not only enhances lung compliance, but also reduces the mechanical power and driving pressures required, thereby potentially decreasing the incidence of ventilator-induced lung injuries (VILI) and improving overall respiratory mechanics[14,15].• Optimizing Mechanical Ventilation: EIT's ability to provide immediate feedback on lung mechanics is crucial for the fine-tuning of mechanical ventilation settings. This feedback helps clinicians balance the need for adequate oxygenation with the risk of exacerbating lung injury, thus significantly impacting patient prognosis.…”
mentioning
confidence: 99%
“…EIT represents a transformative advancement in the management of Acute Respiratory Distress Syndrome (ARDS), a condition characterized by acute hypoxemic respiratory failure and non-cardiogenic pulmonary edema [12]. The complexity of ARDS, with its diverse lung injury patterns, necessitates precise, real-time imaging to guide therapeutic decisions and interventions [13,14].…”
Section: Eit and Ards: Unveiling Pulmonary Inhomogeneitiesmentioning
confidence: 99%
“…This capability allows clinicians to make informed decisions and adjustments based on immediate feedback from the patient's respiratory status. For example, research by Songsangvorn et al has demonstrated that EIT-guided PEEP titration can significantly enhance lung compliance [14]. By using EIT to tailor PEEP settings to the individual patient's needs, clinicians can ensure that the applied PEEP levels are neither too high, which could lead to overdistension, nor too low, which might result in insufficient alveolar recruitment.…”
Section: Eit and Ards: Unveiling Pulmonary Inhomogeneitiesmentioning
confidence: 99%
“…I read the recent meta-analysis by Songsangvorn et al on electrical impedance tomography-guided positive endexpiratory pressure (PEEP) titration in acute respiratory distress syndrome (ARDS) with great interest [1]. While I commend the authors for their excellent work, I have some concerns regarding the meta-analysis.…”
mentioning
confidence: 99%